0
$\begingroup$

Let $$f(x)=\left\{ {\matrix{ {{e^{ - {1 \over {{x^2}}}}},x \ne 0} \cr {0,x = 0} \cr } } \right.$$

Show that $f^{[n]}(0)=0$ for all $n=0,1,2,\cdots$

The proof:
First note that for $x\ne 0$: $f'(x)=\frac{2}{x^3} e^{-\frac{1}{x^2}}$

Consider the polynomial function $P_1(x) = 2x^3$, then we have:

$$f'(x) = P_1\left(\frac{1}{x}\right)e^{-\frac{1}{x^2}}$$

Since,

$$\lim\limits_{x\to 0} \frac{1}{x^n} e^{-\frac{1}{x^2}} = 0 $$

for any integer $n\ge 0$:

$$\lim\limits_{x\to 0} P\left(\frac{1}{x}\right) e^{-\frac{1}{x^2}} = 0 $$

for any polynomial $P(x)$.

Then, by induction we prove there exists $P_n(x)$ such that: $f^{(n)}(x) = P_n\left(\frac{1}{x}\right)e^{-\frac{1}{x^2}}$

My Question:
I don't understand the base case: Why are the two limits approaches $0$? (And where the $\frac{1}{x^n}$ came from?). It looks like black-magic :)

Thanks in advance.

$\endgroup$
  • 1
    $\begingroup$ With a change of variable: $$\lim_{x\to 0}\frac{1}{x^n}e^{-\frac{1}{x^2}}=\lim_{y\to +\infty} y^n e^{-y^2} = 0.$$ The same applies if a polynomial of the variable $1/x$ is took in place of $\frac{1}{x^n}$. $\endgroup$ – Jack D'Aurizio Aug 27 '14 at 19:52
2
$\begingroup$

To make sure consider $u=\frac{1}{x}$. Then 1st limit $$\lim\limits_{u\to \infty} \frac{e^{-u^2}}{u^{n}} \quad \forall n \in \mathbb{N}$$ Using many well-known methods ($\varepsilon-\delta$, for example) you can prove that it is $0$. For better understanding it means that exponential decays faster than any power function. The second is a corollary from the 1st: it's no difference between polynomial or its greater power summand in denominator

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.